The inheritance of Tang Sancai pottery figurines in Luoyang: The integration of traditional handicrafts and the regional cultural background of social transformation - Fei, Liu; Suwanthada, Prathabjai (Edelweiss Applied Science and Technology, 2024)
Creative Documentary Research Data Methodology for mixing the Qualitative Research Methods and collecting research data through surveys, interviews, observations, group discussions and seminars, literature analysis, and field research.to let the educational audience understand and learn the historical background and aesthetic knowledge of Tang Sancai Pottery Figurines. Sancai is a versatile decoration on Chinese pottery and other painted pieces using glazes or slip, predominantly in the three colors of brown (or amber), green, and creamy off-white. Tang Sancai Pottery Figurines is three-colored pottery in Kilns near Xi'an and Luoyang. During the Tang Dynasty, porcelain pottery appeared. Porcelain is ceramic pottery characterized by its white, translucent appearance. It is known for its durability and is often used for making delicate and intricate objects such as vases, bowls, and figurines. This research focused on the inheritance strategy of traditional handicrafts combined with education in the regional cultural regeneration system under the background of China's social transformation. In social transformation, combining traditional handicrafts with modern education and cultivating the educational audience's awareness of protecting traditional culture can not only allow handicraft skills to continue in the classroom. It is also conducive to the survival and development of traditional handicrafts in their place of origin can reshape the regional cultural identity of traditional handicrafts, promote the diversity and innovation of different cultures, traditions, and perspectives, and how to promote cultural diversity, equity, and harmony education and enhance cultural confidence and national identity.